Barriers to Adoption of Commercial Green Buildings in India: A Review. (December 2021) - Saha, Sayani; Hiremath, Rahul B; Prasad, Sanjay; Kumar, Bimlesh
The global construction sector accounts for 13.2% of the world's gross domestic product (GDP). It not only contributes to the economic growth engine of the world but also climate changes due to its high energy footprint. Sustainable buildings have the potential to reduce the adverse impacts of the construction industry, but their adoption is slow due to hindrances. The aim of this paper is to study literature on barriers to green building adoption to date and highlight the overlapping and unique barriers specific to India in comparison to a few prominent countries, and provide solutions and recommendations for future research. The methodology has been an extensive literature review of the barriers to green building (GB) adoption. The key findings, namely barriers, were classified under economic, governmental, organizational and social perception, information, technology and material categories. Barriers unique to India and a few other developing countries are an extension of project schedules, lack of research and developmental works, lack of public motivation, poor building code enforcement, high payback period, uncertain supply of green materials, improper implementation of policy framework and performance of green building technologies (GBT's). The GB construction sector is fragmented around the world. Even the GB definition is not the same across the globe although the environmental aspect is the same. Similarly, there are unique and overlapping challenges in GB adoption globally. Buildings in usage perspectives can be classified into residential and non-residential. This study looks only at non-residential GBs due to their homogenous nature. There is a dearth of specific studies related to the adoption of GBs in India. This study aims to fulfil the gap of India's standing in the barriers to GB adoption with respect to the developed and developing countries. JEL Classification: I18